2017
DOI: 10.1080/00913847.2017.1294012
|View full text |Cite
|
Sign up to set email alerts
|

Primary anterior cruciate ligament reconstruction: perioperative considerations and complications

Abstract: Anterior cruciate ligament (ACL) injuries are among the most commonly studied orthopaedic injuries. Despite having an excellent prognosis, complications do occur. The timely recognition and management of complications is imperative to ensure the success of reconstruction. Avoiding such complications requires thorough preoperative planning, proficient technical skills to properly manage intraoperative complications, and an extensive knowledge of possible postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…The reviewed studies inconsistently reported the physical activity of the ACL-R group as well as the (matched) control group, making an intra-group and inter-study comparison difficult. Possible associated injuries as well as intra- or post-operative complications are present [ 29 ] and might affect the sensorimotor function in different ways. The current review showed that four out of ten studies did not report associated injuries [ 18 , 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed studies inconsistently reported the physical activity of the ACL-R group as well as the (matched) control group, making an intra-group and inter-study comparison difficult. Possible associated injuries as well as intra- or post-operative complications are present [ 29 ] and might affect the sensorimotor function in different ways. The current review showed that four out of ten studies did not report associated injuries [ 18 , 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Complications after ACL-R, such as deep vein thrombosis (DVT), hemarthrosis, effusion and synovitis, infection, or arthrofibrosis are not uncommon. 7 DVT and pulmonary embolism (PE) are relatively rare complications following ACL-R but the incidence of asymptomatic DVT is reported to be closed to 15%. 8 Other studies described a 90-day PE rate of 0.08% and 90-day DVT rate of 0.12% in 301,701 elective arthroscopic procedures.…”
Section: Introductionmentioning
confidence: 99%